Notary's Responsibility for Falsifying the Identity of the Parties in Making the Deed of Foundation Establishment - Anjarsari, Ajeng (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
An authentic deed essentially contains formal truth in accordance with what the parties told the Notary. However, the notary has the obligation to ensure that what is contained in the notarial deed is truly understood and in accordance with the wishes of the parties, namely by reading it so that the contents of the notarial deed become clear. Notaries as public officials are required to be responsible for the authentic deed that they have made. If the authentic deed that they have made occurs after a legal dispute occurs, then this can be questioned, whether the authentic deed was the Notary's mistake, or whether there was an agreement that was made between the Notary and one of them. Formulation of the problem What is the Notary's responsibility in making a deed that contains elements of falsifying the identities of the parties? The research method used is a legislative approach, namely legal research carried out by prioritizing research on library materials or also called secondary materials, in the form of normative law and how to implement it in practice by supported by data, a-data, used in order to obtain materials for analysis related toNotary's responsibility in making foundation deeds for falsifying the identities of the parties. The theories used are the theory of responsibility and the theory of legal certainty. From the results of this research, the responsibility of a Notary in making a deed that contains elements of falsifying the identities of the parties, is that a Notary is responsible for the material truth of the authentic deed he or she makes, if the Notary concerned is involved in a criminal act of falsifying an authentic deed. Information submitted by a party whose material truth is highly doubtful. Notary's testimony regarding the substance of the deed, legal certainty regarding the foundation deed made by the Notary, there is falsification of the identities of the parties, so that the legal certainty of the parties is made by the Notary, there is falsification of the identities of the parties, so this legal certainty also has implications for the position of the deed in the future. Keywords: Documents; Fake; Notary; Protection.